Design of eddy current brake for electric motorcycle braking system - Mufti Reza Aulia Putra; Muhammad Nizam; Dominicus Danardono Dwi Prija Tjahjana (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
Braking systems in motor vehicles generally use a braking system that utilizes friction. The braking performance will decrease caused by using friction rapidly. To overcome this, as an alternative, an electromagnetic braking system can be used by utilizing eddy currents, such as eddy current brakes (ECB). Eddy currents are generated when the rotor pass the magnetic field of the electromagnet. The research aim is to design an ECB system. The performance of the disk design will be determined in this study. The study is about the tendency of the ECB properties. The finite element (FEM) method is used by modeling ECB performance. The experimental results were used to validate the result. The test showed the results of braking using aluminum disk showed the best performance in 12.03 Nm. From these results, the combination of the disks is needed by an appropriate disk design.